(untitled) (Plant Tissue Culture and Biotechnology, 2014)
An efficient protocol for in vitro propagation of an important ornamental terrestrial orchid, Doritis pulcherima Lindl. through axillary shoot and direct protocorm-like body (PLB) formation from shoot tip explants derived from six- month-old axenic seedlings has been described. Shoot tips were cultured on modified nutrient medium of Knudsons C supplemented with 0.1% peptone and combination of various concentrations of NAA and BAP. The effect of NAA and BAP on axillary shoot formation, protocorm-like body induction and root regeneration from the explants was significant. The highest frequency of axillary shoot formation was recorded in the medium containing 2 mg/l BAP and the PLB production was higher in the medium containing 2 mg/l NAA. A higher concentration of BAP showed inhibitory effects on the axillary shoot formation and PLB induction. Efficient root regeneration was observed in low concentration of NAA. However, the profuse root formation was common in the PGR free medium. Rooted plantlets were hardened successfully through the stepwise acclimation protocol and platelets were finally established in the potting mixture containing small pieces of dead tree bark of mango, charcoal pieces and broken bricks in 1 : 2 : 1 ratio. D. O. I. http://dx.doi.org/10.3329/ptcb.v23i2.17526 Plant Tissue Cult. & Biotech. 23(2): 251-261, 2013 (December)